INVESTIGATION OF GEOTHERMAL ENERGY POTENTIAL OF PARTS OF CENTRAL AND NORTH-EASTERN NIGERIA USING SPECTRAL ANALYSIS TECHNIQUE - Odidi, Idena; Mallam, A.; Nasir, N. (FUDMA Journal of Sciences, 2020)
The current study deals with an estimate of the Curie point depth, heat flow and geothermal gradient from spectral analysis of aeromagnetic data covering an area located approximately between latitude 7.5o N to 11.5o N and longitude 7.5o E to 10.5o E, which corresponds to parts of the Benue trough (lower part of the Upper Benue trough, the entire middle Benue trough, and upper part of the Lower Benue trough), lower part of the Gongola and Yola Basins, the Precambrian Basement, the Jurassic Younger Granites and two prominent hot Springs, Wiki hot spring in Bauchi state (in the north-eastern part) and Akiri hot spring in Nasarawa state (in the south-western part) of central and north-eastern Nigeria. Radially power spectrum was applied to the aeromagnetic data of the study area divided into 48 square blocks and each block analysed using the spectral centroid method to obtain depth to the top, centroid and bottom of magnetic sources. The depth values were subsequently used to evaluate the Curie-point depth (CPD), geothermal gradient and near-surface heat flow in the study area. The values of the curie point depths (Zb), range from 7.6341 km to 34.5158 km, with a mean value of 14.7928km, geothermal gradient, range from 16.8039 0C km-1 to 75.97490C km-1, with mean value of 45.7021 0C km-1 and heat flow (q), range from 42.0097 mWm-2 to 189.9372mWm-2, with a mean value of 114.2554mWm-2. Which reveals that, there might probably be good sources for geothermal and thereby further recommended for detailed geothermal exploration.